Metadata: how we relate to images - Mc Sweeney, Anna (Lethaby Gallery, London, 2018)
One might justly claim that metadata is ubiquitous, structuring our interactions with the world in manifold ways. As data about other data, metadata describes and classifies information; among its best-known applications are, for example, library catalogues, maps, or, possibly most familiarly today, the information set — location, time, device — that comes with the simple act of taking a picture on a smartphone.This essay too is metadata. It provides an introduction to the exhibition this booklet accompanies. It will thus influence and inform the way visitors encounter the exhibited objects by providing background information on artworks and suggesting potential links that can be established between them.
An exhibition organised by the International Research Group “Bilderfahrzeuge. Aby Warburg’s Legacy and the Future of Iconology” in collaboration with Central Saint Martins, University of the Arts London
PUBLISHED
Keywords: Manuscript, Book and Print Cultures; History of Art